Web system development based on Laravel and VueJs frameworks for process management: A case study - Avilés Matute, Smith (2020)
Software development involves a high volume of data transfer between web-based applications and the end-user; this requires implementing them using new web technologies. This work contributes to developing a web-based application to improve the process management of the security company UNICEPRI, integrating suitable elements such as the Laravel frameworks for the backend and VueJs for the frontend, and the database manager MariaDB. The Model-View-Controller approach reduces memory resource usage, browsing time, and data recovery by reusing components and partially loading the website, gaining flexibility, and communicating with other applications and hardware. The SCRUM agile methodology was used to follow up on the implementation, allow adequate communication between client and developer, and comply with the different activities in the established times. For the evaluation of the software’s quality, the efficiency metric for the response time according to the ISO / IEC 25010 standard was used, which were analyzed using the t-paired statistical test, resulting in significant system efficiency, improving the management of administrative staff processes within the company.